Simultaneous Analytical Method Of 6-Mercaptopurine and 6-Methylmercaptopurine In-vitro Study With Bio-Sampling Venipuncture and Dried Blood Spot - Yahdiana Harahap (Journal of Global Pharma Technology, 2017)
Objective: 6-Mercaptopurine (6-MP) is a cancer chemotherapeutic agent. Metabolic pathway by thiopurine S-methyltransferase (TPMT) to become 6-methylmercaptopurine (6-MMP).Bio-sampling is required to obtainbiological sample, using two technique; invasive (venipuncture) and minimum invasive(dried blood spot). This study aims to obtain an optimization and validation analysis 6-MP and 6-MMP in vitro study with bio-sampling venipuncture and dried blood spot (DBS). Method: Plasma from venipuncture method extraction was done using dichloromethane. Separation was performed using Waters HPLC, C18 SunfireTM column (5μm, 250 x 4.6 mm), with gradient elution, flow rate 1 mL/min and detected at UV-PDA wavelength of 303 nm. Bio-sampling dried blood spot with DBS CAMAG® paper diameter of 8 mm and extracted with acetonitrile-methanol (1:3). Separation was performed with Waters LC-MS/MS UPLC C18 column (1.7 μm, 2.1 x 100 mm) with gradient elution, flow rate 0.2 mL/min. 5-fluorouracil (5-FU) was used as internal standard.Result: The method venipuncture was linear at concentration range of 2-200 ng/mL for 6-MP and 20-2000 ng/mL for 6-MMP. The method dried blood spot using Waters Xevo TQD for mass detection with positive electrospray ionization (ESI) for 6-MP, 6-MMP and negative ESI for 5-FU in Multiple Reaction Monitoring mode. Linear with the range 26-1000 ng/mL for 6-MP and 13-500 ng/mL for 6-MMP.Conclusion: The developed method is valid for 6-MP and 6-MMP simultaneously in vitro from venipuncture using HPLC and from dried blood spot using LC-MS/MS and showed good selectivity, linearity, accuracy and precision, matrix effect and stability.Keywords: 6-mercaptopurine, 6-methylmercaptopurine, Venipuncture, Dried blood spot.